2008
DOI: 10.2185/jrm.3.45
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Patients with Acute Myocardial Infarction Treated with Percutaneous Coronary Intervention: Comparison of Quality of Life at Discharge and 6 Months after Discharge

Abstract: Objective: The present study investigated the health-related quality of life (QOL) of patients with acute myocardial infarction (AMI) who were treated with percutaneous coronary intervention (PCI). Methods: Forty-three patients were asked to complete the SF-36 questionnaire at discharge and 6 months after discharge. The SF-36 consists of 8 subscales: Physical Functioning (PF), Role Physical (RP), Bodily Pain (BP), General Health perception (GH), Vitality (VT), Social Functioning (SF), Role Emotional (RE), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…However, the scores for GH at discharge were low, and these low scores continued 6 months after discharge ( Table 2 ). Our results were similar to those of previous reports 3 ) .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…However, the scores for GH at discharge were low, and these low scores continued 6 months after discharge ( Table 2 ). Our results were similar to those of previous reports 3 ) .…”
Section: Resultssupporting
confidence: 94%
“…It has also been reported that AMI patients treated with IVCT do not have an improved quality of life (QOL); however, AMI patients treated with PCI have improved QOL. Shibayama 3 ) reported that the physical parameters of health-related QOL improved 6 months after discharge for AMI patients treated with PCI. Janzon 4 ) also reported that the physical QOL scores of patients with unstable angina treated with PCI were higher than for patients with unstable angina treated with IVCT.…”
Section: Introductionmentioning
confidence: 99%